Organizational and economic impact of implementation additive technologies in construction - Hanieiev, Timur; Korzachenko, Mykola; Bolotov, Gennady; Yushchenko, Svitlana (Academic journal Industrial Machine Building Civil Engineering, 2020)
The use of additive technologies in combination with other technologies that provide the transition from model to the finished product is actively used in the industry of many countries. The use of such technologies in combination with casting one allows you to make certain types of sculptures. Modeling of sculptures in specialized software packages without the participation of a sculptor is still not possible, so the most promising direction for town planning is the production of relatively simple in shape models of prominent historical and cultural buildings and entire cities. The ability to 3d print the developed model greatly simplifies and speeds up the production of a master model for further metal casting. The conducted cost analysis showed savings of 15-17% in the transition from manual production of a master model by a sculptor to modeling and 3d printing.
Keywords: additive technologies; economic efficiency; casting; , master model; sculpture